PERTENTANGAN DI ANTARA NASS DENGAN MASLAHAH DAN HUBUNGANNYA DENGAN BID'AH: Contradiction Between Nass and Maslahah and Its Relation to Bid'ah - Ahmad, Ridzwan (Jurnal Syariah, 2011)
The issues of nass, maslahah and bid'ah are always being among the most debatable issues among scholars at any point of time. Even though it has been frequently made a significant agenda in a scholarly discussion since long time ago, these issues seem to be difficult to resolve especially when a fanatic group involved in it to the extent that they rejected any argument against their views aggressively. In Malaysia, these issues are more critical and crucial as the general public who are mostly ignorant of Islam have been exploited to spread their doctrine which aims to gain influence. In consequence, the general public who anticipate the actual religious guidance from the scholars have been more puzzled and confused because this groups considered themselves experts in Syariah ruling. Therefore, this article discusses the real situation of contradiction between nass (revealed text) and maslahah and its relationship with bid'ah (innovation). The concept of bid'ah which is always being perceived as contradictory to al-Sunnah and the practice of al-Salaf al-Salih will be analyzed and thoroughly examined based on the actual understanding of Usul al-Fiqh (Methodology of Islamic Jurisprudence) and Maqasid al-Syari'ah (the objectives of Syariah). This article also emphasizes on the extent to which the correlation between nass and maslahah gives rise to bid'ah hasanah (commendable innovation) as presumed by classical jurists.